Rancangan Sistem Informasi Layanan Administrasi Desa Berbasis Web - Susi Susanti; Diego Wahyu; Ridwan Laksmana; Yuni Eka Achyani (JURIKOM (Jurnal Riset Komputer), 2022)
Sukasih Village is a government agency at the sub-district level, until now it still has several problems in data management, one of which is the process of submitting correspondence for the benefit of the residents is still manual and has the impact of requiring a long processing time until the letter is completed, because residents have to come to the village office repeatedly. times, namely at the time of delivery and at the time of collection of the letter. Another problem is when storing citizen data is still manual and can cause documents to be damaged, lost and the risk of data not being updated. For this reason, it is necessary to have a letter submission information system that can be accessed by interested parties, both within the village and outside the village environment. The design of this system aims to implement and develop a technology information system as a forum for digitizing document submission in Sukaasih Village, in order to overcome or minimize errors in the local community document recording process and can shorten the time associated with administrative services to be easier, faster and more efficient. In designing this website-based document management information system, the system development method used is Rapid Application Development, and the PHP programming language. From the results of the validity test with an r table value of 0.433, the calculated r value for each question is as follows: P1 r count n is 0.4389, P2 r counts N is 0.8568, P3 r counts n is 0.8029 , P4 r count N is 0.8568, P5 r calculates N is 0.8857, P6 r calculates N is 0.8857, P7 r counts N is 0.8029, P8 r counts N is 0.8568, P9 r calculates N is 0.8857, P10 r calculates N is 0.8029, P11 r calculates N is 0.8029, and P12 r calculate the N is 0.4563